Dynamic Redistribution of Mobile Ions in Perovskite Light‐Emitting Diodes. (23rd November 2020) - Wang, Heyong; Chen, Zhan; Hu, Jingcong; Yu, Hongling; Kuang, Chaoyang; Qin, Jiajun; Liu, Xianjie; Lu, Yue; Fahlman, Mats; Hou, Lintao; Liu, Xiao‐Ke; Gao, Feng
Abstract: Despite quick development of perovskite light‐emitting diodes (PeLEDs) during the past few years, the fundamental mechanisms on how ion migration affects device efficiency and stability remain unclear. Here, it is demonstrated that the dynamic redistribution of mobile ions in the emissive layer plays a key role in the performance of PeLEDs and can explain a range of abnormal behaviours commonly observed during the device measurement. The dynamic redistribution of mobile ions changes charge–carrier injection and leads to increased recombination current; at the same time, the ion redistribution also changes charge transport and results in decreased shunt resistance current. As a result, the PeLEDs show hysteresis in external quantum efficiencies (EQEs) and radiance, that is, higher EQEs and radiance during the reverse voltage scan than during the forward scan. In addition, the changes on charge injection and transport induced by the ion redistribution also well explain the rise of the EQE/radiance values under constant driving voltages. The argument is further rationalized by adding extra formamidinium iodide (FAI) into optimized PeLEDs based on FAPbI3, resulting in more significant hysteresis and shorter operational stability of the PeLEDs. Abstract : It is found that the dynamic redistribution of mobile ions modifies the injection and transport property of charge carriers in the emissive layer, which can well explain the hysteresis in external quantum efficiency (EQE)– and radiance–voltage curves, as well as the rise phenomena of EQE and radiance under low constant driving voltages.